Public-Private Collaboration on Productive Development Policies in Argentina - Roberto Bisang; Andrea González; Juan Carlos Hallak; Andrés F. López; Daniela Ramos; Ricardo Rozemberg (Inter-American Development Bank (IDB), 2014)
This study discusses four cases of public-private collaboration (PPC) in the design and implementation of productive development policies (PDP) in Argentina. We find that PPCs have contributed to the success of most of the studied PDPs by facilitating information sharing and creating coordination devices that have improved the diffusion, transparency, and resilience of the policies and a more effective use of public funds. We also identify conditions that seem to be critical for a successful PPC. These conditions include the previous acquaintance and existence of trust relationships among the agents involved in the PPC, the alignment of their objectives and interests, and the emergence of clear leaderships in the private and/or in the public sectors. The stability of the PPCs, in turn, depends on the availability of public funding and the creation of formal governance mechanisms, while it is threatened by large disparities in the size, interests, and capabilities among the different private-sector agents involved in the collaboration.
hdl:11319/6410
Keywords: O25; H11; L56; L8; L6; 330; Productive development policies; Public-Private collaboration; Argentina; Industrial policy; Economic development; institutions